Partitions of groups into sparse subsets - Protasov, I. (Algebra and Discrete Mathematics, 2012)
A subset A of a group G is called sparse if, for every infinite subset X of G, there exists a finite subset F ⊂ X, such that ∩x∈FxA is finite. We denote by η(G) the minimal cardinal such that G can be partitioned in η(G) sparse subsets. If |G| > (κ+)א0 then η(G) > κ, if |G| ≤ κ+ then η(G) ≤ κ. We show also that cov(A) ≥ cf|G| for each sparse subset A of an infinite group G, where cov(A) = min{|X| : G = X A}.